2012
DOI: 10.1007/s11010-012-1513-6
|View full text |Cite
|
Sign up to set email alerts
|

Ectoenzymes and cholinesterase activity and biomarkers of oxidative stress in patients with lung cancer

Abstract: We aimed to examine the nucleoside triphosphate diphosphohydrolases (NTPDase) in lymphocytes; adenosine deaminase (ADA) and butyrylcholinesterase (BChE) in serum; and acetylcholinesterase (AChE), superoxide dismutase (SOD), and catalase (CAT) activity in whole blood; since these enzymes are involved in inflammation responses as well as in oxidative stress conditions. We also checked the levels of total thiols (T-SH), non-protein thiols (NPSH), and thiobarbituric acid reactive substances (TBARS) in serum of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 53 publications
2
23
0
1
Order By: Relevance
“…Taken together, these data suggest that the increased ecto-NTPDase and ADA activities in lymphocytes of hypertensive rats are occurring due to the activation of pro-inflammatory mediators. Alterations in purinergic system enzymes related to other diseases, such as lung cancer, Chagas' disease, experimental sepsis and multiple sclerosis, were already described in recent studies developed by our research group [27,40,44,45].…”
Section: Exercise Prevents Inflammatory Process In Hypertensionmentioning
confidence: 68%
“…Taken together, these data suggest that the increased ecto-NTPDase and ADA activities in lymphocytes of hypertensive rats are occurring due to the activation of pro-inflammatory mediators. Alterations in purinergic system enzymes related to other diseases, such as lung cancer, Chagas' disease, experimental sepsis and multiple sclerosis, were already described in recent studies developed by our research group [27,40,44,45].…”
Section: Exercise Prevents Inflammatory Process In Hypertensionmentioning
confidence: 68%
“…P53 is mutated in ~50% of human cancers and its function as a critical tumor suppressor and in regulation of a large number of genes involved in inhibition of cell proliferation, cell-cycle arrest, apoptosis and senescence, is well-documented 55,56,79 . Several earlier reports showed that the activity of AChE was reduced in lung cancer, likely contributing to lung cancer growth 61,[68][69][70] . Moreover, blocking AChE expression by siRNA or treatment with AChE pharmacological inhibitors, blocked apoptosis 61,71 .…”
Section: Discussionmentioning
confidence: 98%
“…While AChE is not an apoptosis initiator, it acts as a tumor suppressor, in part by the catalytic hydrolysis of acetylcholine 61,[68][69][70] . The activity of AChE was found to be reduced in lung cancer, likely contributing to increased acetylcholine levels, lung cancer growth and tumor aggressiveness, poor prognosis, and low survival rate 61,[68][69][70] . Apoptosis was prevented when using anti-sense oligonucleotides of AChE 71 .…”
mentioning
confidence: 99%
“…The responses of the molecules related to the cholinergic system to inflammation have been studied thoroughly by other authors: the group of Wessler et al (e.g., [48]), the group of Soreq (e.g. [52]), and others (e.g., [53]). On the other hand, CDF/LIF, which enhances the cholinergic differentiation, is involved in the downregulation of immune cell proliferation in case of inflammation.…”
Section: Discussionmentioning
confidence: 99%